A data‐centric capability‐focused approach for system‐of‐systems architecture modeling and analysis. Issue 3 (27th February 2013) - Ge, Bingfeng; Hipel, Keith W.; Yang, Kewei; Chen, Yingwu
Abstract A data‐centric, capability‐focused approach is proposed to facilitate the architecture modeling and analysis of challenging system‐of‐systems (SoS). This approach abstracts essential information from the underlying complexity with the architecture modeling in a data‐centric and semantically consistent fashion, and allows early understanding and exploration of the logical, behavioral, and performance characteristics to achieve the desired capabilities. More specifically, a high‐level data meta‐model, depicting the semantic relationships of constituent architectural data elements, is first presented to guide the architectural data modeling, which is aligned well with the US Department of Defense Architecture Framework (DoDAF) Meta‐model (DM2). Then, the development of architectural descriptions and the construction of executable models are studied based on the core architectural data elements. Additionally, architecture analysis using static and executable models are discussed, including static analysis, dynamic analysis, and experimental analysis. The feasibility of the foregoing approach is demonstrated with an illustrative example. ©2013 Wiley Periodicals, Inc. Syst Eng 16: